Islamic Education Methods in the Quran and Hadith: Approaches in Child Development Guidance - Kusainun, Noven (Journal of Social and Community Development, 2024)
Islamic education aimed at shaping individuals as caliphs must also employ appropriate methods in its implementation. The methods used in Islamic education should adhere to Islamic values to guide and shape students into morally upright individuals. These methods should be grounded in principles derived from the Quran and Hadith. This article aims to explore Islamic educational methods found in the Quran and Hadith, as well as the principles guiding their application. The study identifies several Islamic educational methods, including teaching, dialogue (hiwar), storytelling (qishah), parables (amtsal), role-modeling, habituation, admonition (mau’idzah), reminder, encouragement (targhib), and deterrence (tarhib), all rooted in Islamic teachings. Additionally, it highlights principles such as goal orientation, integration, suitability, truthfulness, flexibility, and dynamism that should guide the application of these methods in Islamic education.